Specificity of "Live High-Train Low" altitude training on exercise performance - Bejder, J.; Nordsborg, N. B. (Exercise and Sport Sciences Reviews, 2018)
The novel hypothesis that "Live High-Train Low" (LHTL) does not improve sport-specific exercise performance (e.g., time trial) is discussed. Indeed, many studies demonstrate improved performance after LHTL but unfortunately control groups are often lacking, leaving open the possibility of training camp effects. Importantly, when control groups, blinding procedures and strict scientific evaluation criteria are applied, LHTL has no detectable effect on performance. It was hypothesized that the scientific evidence supporting that "Live High-Train Low" improves sport-specific exercise performance is weak. ABSTRACT FROM AUTHOR